Not one less - Columbia Pictures Film Production Asia. ([s.l.] Columbia Pictures, 1999)
In the crushing poverty of rural China, a young woman is ordered to a remote village to be their substitute teacher. Barely older than her students, the shy girl is charged with keeping paid. Faced with overwhelming family dept, her biggest little trouble maker disappears into the city to find work. The stubborn teacher, however, is determined to follow the boy and bring him back to school. Once in the city, her simple peasant pleas fall on deaf ears, and only when the local television station sympathizes does her search bear fruit.
VCD
Produced by Zhao Yu ; screenplay by Shi Xiangsheng, directed by Zhang Yimuo
Keywords: Teachers--China.; Feature films